EVALUATION OF IN VITRO ANTI-INFLAMMATORY ACTIVITY OF CITRUS MACROPTERA MONTR - BHUTIA, SONAM (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The use of naturally occurring medicines dependent on essential oils (EOs) is nowadays of great interest. In addition, within the human body, EO shows high efficacy as antioxidants and anti-inflammatory drugs. The present experiment was conducted to access the anti-inflammatory activity of EO obtained from the fruit peels of Citrus macroptera Montr. (Rutaceae) against the denaturation of protein in vitro model. Methods: The test sample (EO) was incubated under controlled laboratory conditions at varying concentrations with egg albumin and was subjected to absorbance determination for the anti-inflammatory property analysis. Diclofenac sodium was used as the standard reference drug for the experiment. Results: The results show a concentration-dependent inhibition of protein (albumin) denaturation by the test oil. This was concluded by comparing their IC50 average values. Citrus macroptera Montr. EO possessed IC50 average value 54.6+0.07 μg/mL, whereas that of diclofenac sodium was found to be 52.89+0.06 μg/ml. The result shows that the test oil is more effective than the standard drug. Conclusion: From the above experimental finding, it can be concluded that Citrus macroptera Montr. EO has significance anti-inflammatory effect against the denaturation of the protein in vitro model. The activity may be due to the presence of terpene polyphenolic component or some other active compound present in the oil. The provided information was first of its kind of knowledge to keep the scientific data for future reference.